First records of Anthidium florentinum (Hymenoptera, Megachilidae) in the Canary Islands: insights on citizen science and exotic bee species - Diego Patiño-Sauma; Carlos Ruiz; John S. Ascher (Journal of Hymenoptera Research)
In recent years, the development of biodiversity inventorying platforms has contributed to the detection of exotic species, bringing awareness to the general public about their impact on native habitats. This is important in the Canary Islands and other oceanic archipelagos, where invasive species pose a great risk to the conservation of ecosystems and biodiversity monitoring strategies may not be completely adequate in their detection. Here we report for the first time the occurrence of the Florentine wool carder bee, Anthidium florentinum, in the Canary Islands and address its current distribution in the islands of Tenerife and Gran Canaria with the help of citizen science. Other bee species recently reported as new to the archipelago through the use of iNaturalist are summarized. The possible effects of A. florentinum on native bee communities in the archipelago, along with the role of cities in hosting biological invasions are also discussed.